Hubungan Pola Penggunaan Masker Medis dengan Mask Acne pada Mahasiswa dan Mahasiswi Universitas Tarumanagara - Feri Yanto Putra; Donatila Mano S (Universitas Malahayati Lampung, 2025)
ABSTRACT The COVID-19 pandemic has affected many aspects of life globally, from daily habits to one's lifestyle. With the prevention regulations against the COVID-19 pandemic, people are wearing masks more often and longer than usual. Thus, it leads to localized acne in the area covered by the mask, popularly called